2022
DOI: 10.1186/s12891-022-05434-2
|View full text |Cite
|
Sign up to set email alerts
|

Can metformin relieve tibiofemoral cartilage volume loss and knee symptoms in overweight knee osteoarthritis patients? Study protocol for a randomized, double-blind, and placebo-controlled trial

Abstract: Background Osteoarthritis (OA) is the most common joint disease, and is most frequently seen in the knees. However, there is no effective therapy to relieve the progression of knee OA. Metformin is a safe, well-tolerated oral medication that is extensively used as first-line therapy for type 2 diabetes. Previous observational studies and basic researches suggested that metformin may have protective effects on knee OA, which needs to be verified by clinical trials. This study, therefore, aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The results of another clinical trial in OA patients confirm the beneficial effects of metformin such as changes in western Ontario and McMaster universities osteoarthritis index (WOMAC) score and visual analog scale (VAS) knee pain with a maximum dose of 2 g/day for 24 months [ 71 ]. In another study, the results showed that metformin (1000 mg/day for 12 weeks) in combination with meloxicam (15 mg/day) significantly improved KOOS components compared to the setting that meloxicam was used alone in OA patients [ 72 ].…”
Section: Discussionmentioning
confidence: 87%
“…The results of another clinical trial in OA patients confirm the beneficial effects of metformin such as changes in western Ontario and McMaster universities osteoarthritis index (WOMAC) score and visual analog scale (VAS) knee pain with a maximum dose of 2 g/day for 24 months [ 71 ]. In another study, the results showed that metformin (1000 mg/day for 12 weeks) in combination with meloxicam (15 mg/day) significantly improved KOOS components compared to the setting that meloxicam was used alone in OA patients [ 72 ].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, several pathways potentially relevant to OA were enriched in our pathway enrichment analysis, implying the biological interpretability of our findings. As no disease-modifying OA drugs (DMOADs) have been approved currently, the demand for developing DMOADs is urgent 65. MR is increasingly becoming a standard tool for triaging new drug targets 66.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, at least two clinical trials (NCT04767841 and NCT05034029) are ongoing to explore the effect of metformin on OA patients. 101 Human platelet-rich plasma Human platelet-rich plasma (hPRP) injections are used increasingly to manage OA. 102,103 hPRP is made by centrifugation of autologous blood so that growth factors and cytokines are released from the α-granules found in the platelets.…”
Section: Metforminmentioning
confidence: 99%
“…Currently, at least two clinical trials (NCT04767841 and NCT05034029) are ongoing to explore the effect of metformin on OA patients. 101 …”
Section: Dmoads Targeting Cartilagementioning
confidence: 99%